TECHNIQUES FOR TRANSLATING CONTENT ON THE RAMADAN EDITION OF THE IKEA INDONESIA WEBSITE - Yessy Purnamasari (Universitas PGRI Palembang, 2024)
The purpose of this study is to determine the translation strategies applied on the IKEA Indonesia website for the Ramadan edition and to examine how those strategies are applied considering Molina and Albir's (2002) theory. 121 items of information were gathered from the Ramadan category on the official IKEA Indonesia website using a qualitative descriptive method. This study was conducted in four stages: collecting data from the Ramadan category on the IKEA Indonesia website, identifying words, phrases, or clauses, then categorizing data according to the translation techniques, and analyzing the use of translation techniques from the categorized data. The results show that among 18 techniques proposed by Molina and Albir, the variation translation technique takes the most frequent used translation techniques in translating the content with the total occurrence of 38 data (31,4%), followed by literal translation technique with 32 data (26,4%), as well as ‘adaptation’ technique that occur in 16 data (13,2%). The implication of his study is both theoretically and practically beneficial for the study of translation.